A hemin-functionalized GroEL nanocage as an artificial peroxidase and its application in chromogenic detection. Issue 16 (5th April 2019) - Wang, Xiaoqiang; Sun, Haiyan; Liu, Chengkun; Wang, Chao
Abstract : Following an inspiration from the chemistry of protein nanocages in nature, we evaluated the performance of a hemin-functionalized GroEL nanocage as peroxidase mimics for chromogenic detection. Abstract : Following an inspiration from the chemistry of protein nanocages in nature, we evaluated the performance of a hemin-functionalized GroEL nanocage as peroxidase mimics for chromogenic detection. The reactivity of this biohybrid formed by detergent dialysis was found to be highly dependent on the amount of hemin encapsulated inside the GroEL central cavity. In comparison with horseradish peroxidase (HRP), the hemin–GroEL complex exhibited a higher recognition ability and reactivity towards the chromogenic substrate tested, while, similar to HRP, the peroxidase mimic followed a ping-pong catalytic mechanism. Moreover, the efficacy of hemin–GroEL for the chromogenic detection of H2 O2 or glucose was demonstrated, with the detection limits determined to be 7 μM for H2 O2 and 11 μM for glucose. This assay was also shown to be useful for the oxidative removal of phenolic compounds. Thus, the GroEL cage is a valuable tool for the development of analytical nano-materials and practical applications such as clinical analysis and environmental monitoring.